2021
DOI: 10.1101/2021.11.17.21266437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experiences of staff providing specialist palliative care during COVID-19A multiple qualitative case study

Abstract: ObjectivesTo explore the experiences of, and impact on, staff working in palliative care during the COVID-19 pandemic.DesignQualitative multiple case study using semi-structured interviews between November 2020 and April 2021 as part of the CovPall study. Data were analysed using thematic framework analysis.SettingOrganisations providing specialist palliative services in any setting.ParticipantsStaff working in specialist palliative care, purposefully sampled by the criteria of role, care setting and COVID-19 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…22 24 During the COVID-19 pandemic, existing challenges were magnified while new constraints were imposed leading to increased levels of moral distress. 4,8,25 This study found that the limited visitation policy, PPE and physical distancing restrictions had a large impact on staff. Facial recognition and lip-reading are important for interpersonal reassurance in distressed patients and the presence of family and friends is well-known to benefit patients with delirium and dementia.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…22 24 During the COVID-19 pandemic, existing challenges were magnified while new constraints were imposed leading to increased levels of moral distress. 4,8,25 This study found that the limited visitation policy, PPE and physical distancing restrictions had a large impact on staff. Facial recognition and lip-reading are important for interpersonal reassurance in distressed patients and the presence of family and friends is well-known to benefit patients with delirium and dementia.…”
Section: Discussionmentioning
confidence: 72%
“…The moral distress doctors described had varying effects but at its worst, caused feelings of guilt and ineffectiveness, which supports previous research into the effects of moral distress. 8,22 Experiencing moral distress can lead to what is termed moral residue, the lingering emotional wound that can result, 27,28 or moral injury which has been defined as the profound psychological distress that follows when a person’s moral or ethical code is violated by actions, or lack of actions, taken. 29 The potential for moral injury is evident in the doctors’ accounts and may have profound consequences on their professional and personal well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation